Buddhist Engagement with the Muaro Jambi Temple Complex and Its Impact on Religious Identity and Socio-Economic Development - Sulani, Puji; Sulaiman, Sulaiman; Jiwanda, Jatayu; Setyawati, Rini (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
The Muaro Jambi temple complex, once a major Buddhist center during the Srivijaya Kingdom, continues to shape the socio-religious identity of the Buddhist community while contributing to local socio-economic development. This study examines contemporary Buddhist engagement with the site, focusing on its role in religious identity formation, educational utilization, and economic impact. Using an explanatory qualitative approach with an intrinsic case study strategy, data were collected through in-depth interviews, documentation, and observations, ensuring validity through triangulation techniques. Findings reveal that religious activities such as Vesak celebrations, meditation retreats, and dharmayatra pilgrimage have reinforced Buddhist communal identity, while the temple complex also serves as an educational hub integrated into Buddhist curricula and historical studies. Additionally, its function as a religious tourism site has boosted local economic activities, though challenges remain in ensuring sustainable local community involvement. Using Parsons’ social action theory, this study illustrates how religious, cultural, and economic dimensions interact within structured social systems. These findings contribute to discussions on heritage preservation, religious identity, and sustainable cultural tourism, highlighting the importance of integrating religious heritage management with community-based development strategies.